NEW MEDIA ARTS AND THE FUTURE OF TECHNOLOGIES. - Candy, Linda (Communications of the ACM, 2007)
The article discusses how software design can support creative endeavors. Photoshop is presented as a good example of software that permits expression of varying levels of creativity without bogging the user down with technical details. Engineer Andrew Johnston and composer Ben Marks have collaborated on software that produces sound and visual images corresponding to instrumental or vocal music. Their software was produced piecemeal and in an exploratory manner involving musicians. The process of software development for creative purposes should spawn a vocabulary of its own, including such terms as playability, seductivity, and fluency.